Weighing the Value of the Bargain: Prosecutorial Discretion After Sentencing Guidelines - Vance, Stephen E. (Criminal justice policy review, 2019)
There is little empirical research to indicate whether the introduction of sentencing guidelines displaces discretion from judges to prosecutors. In the handful of studies that examine the hydraulic displacement of discretion, discretion is usually measured by the rate of charge bargaining. The current study uses an alternative methodology—calculating the value of the bargain—to examine the effect of sentencing guidelines on prosecutorial discretion in the District of Columbia Superior Court. It measures the impact of charge bargaining on sentence length in a sample of 266 pre-guidelines sentences and 263 post-guidelines sentences, and finds that the rate of charge bargaining did not change after the introduction of guidelines, but that the impact of bargaining on sentence length increased slightly. Although the amount of displacement of discretion in the D.C. Guidelines was modest, the study demonstrates that alternative measures (value of the bargain) might reveal displacement of discretion when traditional measures (rate of the bargain) do not.